511 Barriers and enablers to switching from a solid to a liquid formulation of Parkinson's medication: A theory-based mixed methods investigation. (13th April 2023) - Smith, C; Atkins, B; Bhattacharya, D; Scott, S
Abstract: Introduction: Swallowing tablets/capsules can become difficult and dangerous for People with Parkinson's (PwP) who develop oropharyngeal dysphagia(1). Switching to a liquid delays the need for progressing to last line patches/injections. However, liquids are rarely used therefore a change in prescribing practice is warranted but, as with any change in behaviour, may be met with resistance. Aim: To characterise PwPs and carers' barriers and enablers (determinants) of switching from solid to liquid Parkinson's medication formulations. Methods: Underpinned by the Theoretical Domains Framework, focus groups with PwPs and carers from across the UK were convened to identify determinants of switching. Carers were included in focus group discussions as they are often involved in supporting administration of medication(1). A semi-structured topic guide was developed and piloted which asked open questions on participants' thoughts and feelings about switching to liquid medicines. Focus group discussions were analysed and data inductively coded as barriers and enablers to switching from solid to liquid medication. Guided by the TDF domain definitions, the inductive codes were then mapped to the relevant TDF domain(s). An online questionnaire was developed to measure the importance and generalisability of the identified barriers and enablers to switching. The questionnaire was developed based on the barriers and enablers to switching identified in the focus groups. Questionnaire item(s) were generated for each identified barrier and enabler within the relevant TDF domain to measure the extent to which they influenced the decision to switch. Patient and Public Involvement members piloted the questionnaire to identify any difficulties interpreting items and formulating responses. Determinants were prioritised if ≥50% of respondents agreed/strongly agreed that they were important to their decision to switch to a liquid formulation. Percentage precisions were reported as 95% confidence intervals. Results: From the three focus groups six themes were generated: (1) the process of change; (2) impact on lifestyle; (3) margin for error; (4) reflections on ability to administer; (5) position in treatment pathway and (6) curiosities. 131 questionnaire responses from PwPs and carers prioritised nine determinants. Three enablers had almost unanimous agreement: liquids' flexibility for incremental dosing (72% ±8); decline in Parkinson's control (72% ±8); prescriber's endorsement to switch (70% ±8). Two of the barriers: perception that tablets/capsules are easier to dose than liquids (72% ±8); and prescriber's opposition to switching (70% ±8), attracted similarly high agreement. Conclusion: There is a desire to switch to liquids when Parkinson's progresses and for their use beyond this to offer flexibility in dosing, a previously unrecognised indication for switching. The only notable resistance to switching may be addressed by innovations from the pharmaceutical industry to make liquids easier to measure. The influencers of switching to a liquid version of a Parkinson's medication that require addressing are mapped to 40 Behaviour Change Techniques. This provides an evidence and theory-based framework from which strategies may be selected to support a safe and acceptable switch(2). References: 1. Kwon M, Lee JH. Oro-Pharyngeal Dysphagia in Parkinson's Disease and Related Movement Disorders. JMD. 2019 Sep 30;12(3):152–60. 2. Atkins B, Bhattacharya D, Smith C, Scott S. Barriers and enablers to switching from a solid to a liquid formulation of Parkinson's medication: a theory-based mixed methods investigation. Int J Clin Pharm. 2022 Aug;44(4):1046–56.